Pembinaan Keagamaan dalam Lingkungan Keluarga Pengasuh Anak Korban Perceraian - Mimi Delfia; Syaflin Halim; Rahmi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
Children Divorce victims are faced with a variety of life problems that boil down to their future, to realize a bright future inseparable from education, this study aims to describe how the methods used as well as the material that the caregiver's family teaches to the child of the divorce victim in the family environment. This research was conducted with qualitative approach, data source consisting of parents of child caregivers divorce victims, children who are victims of divorce, public figures who are purposively selected. Data collection techniques are carried out by observation, interviews and documentation studies. The results prove that there are several methods used by the caregivers of divorce victims in teaching Islam in the family environment such as the method of nudity, the method of story of the total method of pysik response. Adapaun Islamic religious material taught to children of divorce victims in the family environment is related to faith, worship, morals, but this material is not systematically regulated and not taught in stages